DIW Berlin Economic Outlook: Global economy experiencing robust growth; Germany's recovery is delayed further - Timm Bönke; Guido Baldi; Hella Engerer; Pia Hüttl; Konstantin Kholodilin; Frederik Kurcz; Violetta Kuzmova-Anand; Theresa Neef; Laura Pagenhardt; Werner Röger; Marie Rullière; Jan-Christopher Scherer; et al. (DIW Weekly Report, 2024)
The German economy will likely contract in the first quarter of 2024 due to still heightened inflation and weak demand, which was already weighing on German economic output in 2023. Inflation, which is falling in both Germany and the euro area overall, is expected to return close to the European Central Bank's two-percent target, suggesting that a turnaround in interest rates can be expected in early summer. Better financing conditions and the slowdown in price momentum are likely to somewhat boost both private consumption as well as corporate investments over the course of 2024. Nevertheless, there is currently still a great deal of uncertainty, particular in regard to the future economic policy environment, which is causing households and companies to remain cautious in Germany. In addition, fiscal policy stimuli as well as foreign demand are lacking. German GDP will virtually stagnate and, carried by private consumption and public investments in equipment, increase more markedly by 1.2 percent in 2025. The global economy will continue to develop more robustly than Germany; it is projected to increase by 3.5 percent in both 2024 and 2025, which should gradually strengthen German exports.
Keywords: E32; E66; F01; 330; Business cycle forecast; economic outlook